Triglav 240 - Lačen Benedičič, Irena; Marija Kunstelj, Ana; Mikša, Peter; Ogrin, Matej; Zorn, Matija (ZRC SAZU, Založba ZRC, 2018)
The volume is dedicated to the 240th anniversary of the first documented ascent to Mount Triglav. It contains about thirty chapters that highlight new discoveries about Mount Triglav as a mountain, a myth and a symbol. Mount Triglav and its surrounding are presented from the geographical, historical, ethnological, as well as sports and mountaineering aspects.